2013
DOI: 10.1088/1674-1137/37/11/117002
|View full text |Cite
|
Sign up to set email alerts
|

Study on collimation and shielding of the back-streaming neutrons at the CSNS target

Abstract: The back-streaming neutrons from the spallation target at CSNS are very intense, and can pose serious damage problems for the devices in the accelerator-target interface region. To tackle the problems, a possible scheme for this region was studied, namely a specially designed optics for the proton beam line produces two beam waists, and two collimators are placed at the two waist positions to maximize the collimation effect of the back-streaming neutrons. Detailed Monte Carlo simulations with the beams in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 11 publications
(10 reference statements)
0
3
0
Order By: Relevance
“…It is also capable of supporting multiple platforms, such as the application of high energy protons, muon beam and white neutron beam [6]. A beam line exploiting the backstreaming neutrons, named Back-n, is built mainly for the nuclear data measurements and started running simultaneously with CSNS in 2018 [7][8][9][10]. The neutron energy spectrum of Back-n is characterized since it is of great im- * e-mail: baojie_ciae@126.com portance for feasibility study and analysis for the measurements.…”
Section: Introductionmentioning
confidence: 99%
“…It is also capable of supporting multiple platforms, such as the application of high energy protons, muon beam and white neutron beam [6]. A beam line exploiting the backstreaming neutrons, named Back-n, is built mainly for the nuclear data measurements and started running simultaneously with CSNS in 2018 [7][8][9][10]. The neutron energy spectrum of Back-n is characterized since it is of great im- * e-mail: baojie_ciae@126.com portance for feasibility study and analysis for the measurements.…”
Section: Introductionmentioning
confidence: 99%
“…Earlier studies show that the back-streaming neutrons from the spallation target is very much suitable to be exploited as a white neutron source for nuclear data measurements [4][5][6][7][8]. With rapid development of nuclear energy in China, especially for next-generation reactors, very strong and eminent demand for much enhanced nuclear database has been increasing.…”
Section: Introductionmentioning
confidence: 99%
“…The backstreaming neutrons from the spallation target of CSNS are very strong and harmful to the devices in the proton beam transport line if they are not well treated [7]. However, the studies found that the neutron beam has excellent properties in energy spectrum and time structure, and it has been proposed to build a white neutron beam line or white neutron source (WNS) for nuclear data measurements [8], which is now under construction.…”
Section: Introductionmentioning
confidence: 99%